Matrix regularization for tensor fields. (13th December 2022) - Adachi, Hiroyuki; Ishiki, Goro; Kanno, Satoshi; Matsumoto, Takaki
Abstract: We propose a novel matrix regularization for tensor fields. In this regularization, tensor fields are described as rectangular matrices, and area-preserving diffeomorphisms and local rotations of the orthonormal frame are both realized as unitary similarity transformations of matrices in a unified way. We also show that the matrix commutator corresponds to the covariantized Poisson bracket for tensor fields in the large- N limit.